2018
DOI: 10.1103/physreva.98.042125
|View full text |Cite
|
Sign up to set email alerts
|

Noise-induced non-Markovianity

Abstract: We have studied the non-Markovianity of dichotomously driven spin-boson model in the strong coupling regime in both memory kernel and time convolutionless master equation formulations. A strong correlation between the decay time of the environmental correlation function and the nonzero non-Markovianity is found in the absence of the external noise. Stochastic driving is shown to create strong non-Markovianity when the dynamics of the system without driving is Markovian.Also, exact analytical expressions for th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The non-Markovianity of the dynamics due to DMN has also be thoroughly demonstrated [63,64]. The effect of DMN on the non-Markovianity of a spin embedded in a bosonic bath was demonstrated in [65]. In particular, it was shown that classical noise can create strong non-Markovianity when the dynamics of the noise-free system is Markovian.…”
Section: Correlation Functionmentioning
confidence: 94%
“…The non-Markovianity of the dynamics due to DMN has also be thoroughly demonstrated [63,64]. The effect of DMN on the non-Markovianity of a spin embedded in a bosonic bath was demonstrated in [65]. In particular, it was shown that classical noise can create strong non-Markovianity when the dynamics of the noise-free system is Markovian.…”
Section: Correlation Functionmentioning
confidence: 94%
“…Equation (22) can be used to further analyse the behaviour of the non-Markovianity N in the weak coupling limit. First note that for α = 0 the time evolution is unitary, and thus, N = 0.…”
Section: Non-analyticity Of the Non-markovianitymentioning
confidence: 99%
“…Previous studies of non-Markovianity in the spin-boson model used perturbative approaches or focused on special parameter regimes such as higher temperature. [18][19][20][21][22] We also mention a path-integral study of non-Markovianity in a related model, 23 albeit for finite temperature, and a very recent, similar investigation in the integrable model of quantum Brownian motion. 24 The spin-boson model, which involves a two-level system (or spin) interacting linearly with a bath of harmonic oscillators, is a paradigmatic model to describe dissipative quantum dynamics.…”
mentioning
confidence: 99%
“…The effect of RTN on transport via continuous-time quantum walks has been studied on lattices [30,31], also in presence of spatial correlations [32]. Its effect on the non-Markovianity of the dynamics of the spin-boson model has also been considered [33].…”
Section: Introductionmentioning
confidence: 99%